Increased plasmablasts enhance T cell-mediated beta cell destruction and promote the development of type 1 diabetes - Ling, Qing; Shen, Lei; Zhang, Wei; Qu, DuoDuo; Wang, Hongdong; Wang, Bin; Liu, Yong; Lu, Jing; Zhu, Dalong; Bi, Yan (Molecular medicine (Cambridge, Mass.), 2022)
Although type 1 diabetes (T1D) is typically described as a T cell-mediated autoimmune disease, increasing evidence for a role of B cells has emerged. However, the pivotal disease-relevant B cell subset and its contribution to islet autoimmunity remain elusive. The frequencies and phenotypic characteristics of circulating B cell subsets were analyzed using flow cytometry in individuals with new-onset T1D, long-term T1D, type 2 diabetes, and nondiabetic controls, and also in a prospective cohort of patients receiving mesenchymal stromal cell (MSC) transplantation. NOD mice and adoptive transfer assay were used to dissect the role of the certain B cell subset in disease progression. An in-vitro coculture system of islets with immune cells was established to examine the response against islets and the underlying mechanisms. We identified that plasmablasts, a B cell subset at the antibody-secreting stage, were significantly increased and correlated with the deterioration of beta cell function in patients with new-onset T1D. Further, a fall of plasmablast number was associated with the preservation of beta cell function in patients who received MSC transplantation after 3 months of follow-up. Meanwhile, a gradual increase of plasmablasts in pancreatic lymph nodes during the natural progression of insulitis was observed in non-obese diabetic (NOD) mice; adoptive transfer of plasmablasts together with T cells from NOD mice accelerated diabetes onset in NOD/SCID recipients. Our study revealed that plasmablasts may function as antigen-presenting cells and promote the activation and proinflammatory response of CD4 T cells, further contributing to the T cell-mediated beta cell destruction. Our results provide insights into the pathogenic role of plasmablasts in islet autoimmunity and may offer new translational strategies for inhibiting T1D development.